Injury patterns following simple elbow dislocation: radiological analysis implies existence of a pure valgus dislocation mechanism - Schnetzke, Marc; Ellwein, Alexander; Maier, Dirk; Wagner, Ferdinand Christian; Grützner, Paul Alfred; Gühring, Thorsten (Archives of orthopaedic and trauma surgery, 2021)
The aim of the present study was to analyze the injury pattern and thus the dislocation mechanism after simple elbow dislocation using radiographs and magnetic resonance imaging (MRI) data sets.
Published online: 11 August 2020
Gesehen am 25.11.2021